PRAKTIK KONSTRUKSI JENDER DI MEDIA MASSA - Lilik Wahyuni (LITERA, 2014)
The mass media is part of one of the class systems. Therefore, it becomes one of thedomination system arenas, one of which is the patriarchal norm domination. Through themass media, society carries out a symbolic contestation such as daily linguistic exchangesto construct gender. This study aims to explain: (1) verbal forms of gender construction, (2)dynamics of gender construction, and (3) gender trajectory in the mass media. The studyemployed the qualitative approach, discourse analysis, and Gadamer’s hermeneutics.Based on the analysis, the findings are as follows. First, verbal forms of gender constructionin the mass media are represented by forms of diction and expression styles showingsymbolic contestation between males and females. Second, in the mass media, there aredynamics of the maintenance and replacement of doksa. Third, the gender trajectory inthe mass media includes ideological changes and divided awareness.